2016
DOI: 10.1038/srep33430
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Development of Gut Microbiota in Triclocarban Exposed Pregnant and Neonatal Rats

Abstract: Alteration of gut microbial colonization process may influence susceptibility of the newborn/infant to infectious and chronic disease. Infectious disease risk leads to widespread use of non-prescription antimicrobials in household products such as Triclocarban (TCC), an antimicrobial compound in personal care products. TCC concentrates in and is transferred through the milk to suckling offspring. TCC exposure during gestation and lactation significantly reduced phylogenetic diversity (PD) among exposed dams an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Adolescent rats receiving oral triclosan at levels comparable to human exposures develop lower microbial diversity in the gut and more prominent changes in taxonomic composition than in adult rats (Hu et al , ). While triclocarban exposures are less studied, in pregnant rats and their offspring < 10 days old exposure leads to lowered phylogenetic diversity and revealed a dominance of the Proteobacteria phylum in the gut (Kennedy et al , ). In a small, randomized, crossover human study, TC wash product exposure did not induce major perturbations of the oral and gut microbiomes (Poole et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent rats receiving oral triclosan at levels comparable to human exposures develop lower microbial diversity in the gut and more prominent changes in taxonomic composition than in adult rats (Hu et al , ). While triclocarban exposures are less studied, in pregnant rats and their offspring < 10 days old exposure leads to lowered phylogenetic diversity and revealed a dominance of the Proteobacteria phylum in the gut (Kennedy et al , ). In a small, randomized, crossover human study, TC wash product exposure did not induce major perturbations of the oral and gut microbiomes (Poole et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that exposure to TCC results in adverse effects on the gastrointestinal tract of neonate mice. Acute gastric ulcers and dysbiosis of gut microbiota have been observed in neonate mice directly or indirectly absorbing TCC during pregnancy or lactation . In human intestinal epithelial cell lines, ER stress is triggered, and apoptosis is induced by 4‐NP, a common contaminant in environment .…”
Section: Discussionmentioning
confidence: 99%
“…There is a complex relationship among the maternal, nutritional, and developmental events that surround the seeding of the neonatal microbiome (Miller, 2016;Ganal-Vonarburg et al, 2017). These events have also been evaluated to some extent in neonates of nonclinical species, including the rat (Kennedy et al, 2016;Ganal-Vonarburg et al, 2017), dog (Guard et al, 2017), pig (Saraf et al, 2017), and rhesus macaque (Ardeshir et al, 2014).…”
Section: Neonatal Microbiomementioning
confidence: 99%
“…When considering the ADME characteristics of the neonatal gastrointestinal system, it is important to also consider the potential role of the neonatal microbiome. This is especially important given the relatively high risk of infection in neonates, the current use of peripartum antimicrobial agents in mothers and neonates, and the potential role of microbiota in the metabolism of both nutrients and medicines (Sherman et al, 2014;Kennedy et al, 2016;Macpherson et al, 2017;Nogacka et al, 2017).…”
Section: Neonatal Microbiomementioning
confidence: 99%